A method to acquire CT organ dose map using OSL dosimeters and ATOM anthropomorphic phantoms. Issue 8 (24th July 2013) - Zhang, Da; Li, Xinhua; Gao, Yiming; Xu, X. George; Liu, Bob
Abstract : Purpose: : To present the design and procedure of an experimental method for acquiring densely sampled organ dose map for CT applications, based on optically stimulated luminescence (OSL) dosimeters "nanoDots" and standard ATOM anthropomorphic phantoms; and to provide the results of applying the method—a dose data set with good statistics for the comparison with Monte Carlo simulation result in the future. Methods: : A standard ATOM phantom has densely located holes (in 3 × 3 cm or 1.5 × 1.5 cm grids), which are too small (5 mm in diameter) to host many types of dosimeters, including the nanoDots. The authors modified the conventional way in which nanoDots are used, by removing the OSL disks from the holders before inserting them inside a standard ATOM phantom for dose measurements. The authors solved three technical difficulties introduced by this modification: (1) energy dependent dose calibration for raw OSL readings; (2) influence of the brief background exposure of OSL disks to dimmed room light; (3) correct pairing between the dose readings and measurement locations. The authors acquired 100 dose measurements at various positions in the phantom, which was scanned using a clinical chest protocol with both angular and z ‐axis tube current modulations. Results: : Dose calibration was performed according to the beam qualities inside the phantom as determined from an established Monte Carlo model of the scanner. The influence of the brief exposure to dimmed room light was evaluated and deemed negligible. Pairing between the OSL readings and measurement locations was ensured by the experimental design. The organ doses measured for a routine adult chest scan protocol ranged from 9.4 to 18.8 mGy, depending on the composition, location, and surrounding anatomy of the organs. The dose distribution across different slices of the phantom strongly depended on the z ‐axis mA modulation. In the same slice, doses to the soft tissues other than the spinal cord demonstrated relatively small variations, with the maximum COV around 11.4%. This might be attributed to the angular mA modulation, the placement of the dosimeters, the chest cavity of the scanned region, and the size of the phantom. Doses to the spinal cord were consistently lower than those to other soft tissues. Conclusions: : The method is suited for acquiring densely sampled organ dose maps, and can be used for studying dose distributions relevant to subject size, organ location, and clinical CT protocols.